A Lady like Sarah : A Rocky Creek Romance - Brownley, Margaret (Nashville : Thomas Nelson, 2009)
Justin Wells heads out alone on the dusty trail to Texas, but when the once-respected clergyman encounters a feisty redhead, Sarah Prescott, in handcuffs with a dying U.S. Marshal at her side, their journey takes a dramatic turn.
"Includes reading group guide"--P. [4] of cover.
Keywords: Women -- Fiction; Clergy -- Fiction; Middle West -- Fiction -- History; Western stories; Love stories; Fiction